Water Footprint of Table Grape Production Systems: A Review of South African and Global Studies - Sigadla, A.; Avenant, E.; Fanadzo, M.; Kangueehi, G.N.; Avenant, J.H. (South African Journal of Enology and Viticulture, 2022)
Being a water-scarce country, South Africa (SA) faces several water challenges, including drought and other effects of climate change. Therefore, there is a need to improve water-use efficiency (WUE) by accurately quantifying the water use and WUE of table grape vineyards. The objective of this review is to (i) provide an overview of water footprint (WF) studies conducted on table grape production systems in SA and globally; (ii) identify limitations in current WF assessments of table grape production systems; and (iii) establish a range of WF values for table grape production systems as an indicator of WUE and for use in decision-making regarding sustainable freshwater use. The review has demonstrated that only a limited number of detailed WF studies have been undertaken on table grapes in SA and globally. Region-specific lookup tables for quantifying blue, green and grey water use in table grape production systems are available for three table grape production regions of SA and could be used for future WF assessments. Most global studies conducted on grape WF and WUE were desktop studies and did not include actual field records from production units, nor did they distinguish between different grape types (table, raisin and wine grapes). WF values must be interpreted in context, specifically regarding the water used versus yield, quality and income, as well as the region, climatic conditions, soil characteristics, irrigation and cultivation practices. For future WF and WUE assessments, a more detailed breakdown of water use is recommended, both during the production process and postharvest.